ANALISIS PERTUMBUHAN EKONOMI DAN INDEKS PEMBANGUNAN MANUSIA (IPM) PROVINSI-PROVINSI DI INDONESIA (METODE KOINTEGRASI) - Eka Pratiwi Lumbantoruan; Paidi Hidayat (Ekonomi dan Keuangan, 2014)
The purpose of this research is to see patterns and long-term relationship between economic growth and human development index (HDI) provinces in Indonesia during the period 2004-2011 by using Klassen Typology to see the patterns and Cointegration test method to see the long-term relationship. The results showed that by using Klassen Typology, there are 8 provinces in the category of fast forward and fast growing (quadrant I). For the category of fast growing area (quadrant II) there are 12 provinces and regions in the category of advanced but depressed (quadrant III) by 6 provinces. For the category of relatively underdeveloped (quadrant IV) there are 7 provinces. Meanwhile, the results of cointegration test showed a long-term equilibrium relationship between Economic Growth and Human Development Index (HDI) in the Indonesian provinces.Keywords : Klassen Typology, Cointegration test, Economic Growth,Human Development Index.